2019
DOI: 10.1002/jctb.6262
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic hydrolysis of cellulose to total reducing sugars with superior recyclable magnetic multifunctional MCMB‐based solid acid as a catalyst

Abstract: BACKGROUND: Effective cellulose hydrolysis has a huge potential for producing high value-added biomass-based platform chemicals, such as glucose, hydroxymethylfurfural, levulinic acid, and total reducing sugars (TRS). Particularly, a magnetic multifunctional solid acid catalyst (Fe 3 O 4 /Cl-MCMB-SO 3 H) was synthesized by loading the active groups on the magnetic mesocarbon microbead (MCMB) derived from the co-calcination of coal tar pitch and ferroferric oxide, which was applied as a catalyst in the conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The efficiency of cellulose hydrolysis increases with the increase of the electronegativity (-NO 2 > -Cl > -NH 2 > -Br) of the binding groups ( Han et al, 2019 ), which is consistent with the observation by Shuai and Pan ( Shuai et al, 2012 ). A series of solid acid catalysts bearing -Cl were synthesized with different methods and enhanced glucose yields by about 2.5 times (93%) compared to the catalysts without -Cl (37%) ( Pang et al, 2014 ; Shen et al, 2014 ; Zhao et al, 2014 ; Zuo et al, 2014 ; Hu et al, 2016 ; Yang et al, 2016 ; Shen et al, 2017 ; Shen et al, 2018 ; Ding et al, 2019 ; Li et al, 2020 ; Li et al, 2020 ). These catalysts follow the same binding mechanism that proposed above for promoting cellulose hydrolysis efficiency.…”
Section: Cellulase-mimetic Catalystsmentioning
confidence: 99%
“…The efficiency of cellulose hydrolysis increases with the increase of the electronegativity (-NO 2 > -Cl > -NH 2 > -Br) of the binding groups ( Han et al, 2019 ), which is consistent with the observation by Shuai and Pan ( Shuai et al, 2012 ). A series of solid acid catalysts bearing -Cl were synthesized with different methods and enhanced glucose yields by about 2.5 times (93%) compared to the catalysts without -Cl (37%) ( Pang et al, 2014 ; Shen et al, 2014 ; Zhao et al, 2014 ; Zuo et al, 2014 ; Hu et al, 2016 ; Yang et al, 2016 ; Shen et al, 2017 ; Shen et al, 2018 ; Ding et al, 2019 ; Li et al, 2020 ; Li et al, 2020 ). These catalysts follow the same binding mechanism that proposed above for promoting cellulose hydrolysis efficiency.…”
Section: Cellulase-mimetic Catalystsmentioning
confidence: 99%
“…Seeing that efficient and easy separation are the main features of heterogeneous catalysts, incorporating magnetic properties into biomass-derived solid catalysts is to be considered. It was found that the recovery rate of magnetic solid catalysts was 1.7-fold higher than non-magnetic solid catalysts (Abida et al, 2020;Li et al, 2020;Xie & Wan, 2018). Araujo et al (2021) successfully inserted the magnetic behaviour into acai seedderived carbon material using the impregnation process followed by carbonization and sulfonation, and red mud was used as the magnetic source.…”
Section: Introductionmentioning
confidence: 99%
“…Mesocarbon microbeads (MCMBs) are recognized as a kind of soft carbon with good sphericity, uniform particle size distribution, ease of graphitization, and other special properties [ 1 ]. MCMBs are accepted as a suitable precursor widely applied in a lithium-ion battery [ 1 , 2 ], lithium-ion supercapacitor [ 3 ], Li-S battery [ 4 ], sodium-ion battery [ 5 ], MCMB–SiC composite ceramic [ 6 ], solid acid catalyst [ 7 ], photocatalyst [ 8 ], and so on. In other words, MCMBs are one of the most important functional artificial carbon materials widely used in the metallurgy industry, chemical industry, aerospace industry, energy storage, and catalysis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%